The Place of Devotion : Siting and Experiencing Divinity in Bengal-Vaishnavism - Sarbadhikary, Sukanya, 1983- (Book collections on Project MUSE., 2015)
"The anthropology of Hinduism has amply established that Hindus have strong involvement with sacred geography. The Hindu sacred topography is dotted with innumerable pilgrimage places, and popular Hinduism is abundant with spatial imaginings. Thus Shiva and his partner, the mother goddess, live in the Himalayas, goddesses descend on earth as beautiful rivers, the goddess Kali's body parts are imagined to have fallen in various sites of Hindu geography sanctifying them as sacred centres, and yogis meditate in forests. Bengal similarly has a thriving culture of exalting sacred centres and pilgrimage places, one of the most important among them being the Navadvip-Mayapur sacred complex, Bengal's greatest site of guru-centred Vaishnavite pilgrimage and devotional life. The main question my book seeks to answer is what sites and senses of place beyond physical geographical ones can do to our notions of space/place, affect, and sanctity. While the contemporary anthropology of place and embodiment, following Edward Casey's philosophy (1993), is dominated by the idea of body-in-place, my book seeks to extend his formulations by also analysing cultural constructions and experiences of place in the body, mind etc. Traveling through both exterior and interior landscapes, I show that the practitioner inhabits Krishna's world through every daily religious practice. The synaesthesia that results from the overlap of these different planes of experience confirms the intensely transformative power of Vaishnava ritual processes"--Provided by publisher